2015
DOI: 10.4049/jimmunol.1500559
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan–Activated Human B Lymphocytes Participate in Innate Immune Responses by Releasing Proinflammatory Cytokines and Stimulating Neutrophil Chemotaxis

Abstract: B-lymphocytes play an essential regulatory role in the adaptive immune response through antibody production during infection. A less known function of B-lymphocytes is their ability to respond directly to infectious antigens through stimulation of pattern recognition receptors expressed on their surfaces. β-glucans are carbohydrates present in the cell wall of many pathogenic fungi that can be detected in the peripheral blood of patients during infection. They have been shown to participate in the innate infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 47 publications
(58 reference statements)
6
54
1
5
Order By: Relevance
“…; Ali et al. ). Then, we assessed NO production by stimulated PBMC, since iNOS‐derived NO is an important cellular signaling molecule secreted as free radical (Lechner et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Ali et al. ). Then, we assessed NO production by stimulated PBMC, since iNOS‐derived NO is an important cellular signaling molecule secreted as free radical (Lechner et al.…”
Section: Discussionmentioning
confidence: 98%
“…Human monocyte-derived β-glucan from baker's yeast (Cardone et al, 2014) Agilent-014850 Whole Human RPS18, EGR1, NFKBID, DCs from healthy donors (Sigma-Aldrich) 10 µg mL IL12B,IL12A,EB13,ITGB8,IL27,IL15,CD38,CD80,CCR7,STAT3,IRF1,TNF,CCL4,IL10,IL20,IL23,NFKB1A,NFKBIZ,PTGS2,TLR2,SOD2,NFKB1,IL6,IL1B,IL6,IL8,IL12, Human B lymphocytes Curdlan (Sigma-Aldrich) (Ali et al, 2015) IL-8 expression was shown to IL18 isolated from healthy 100 ug mL −1 for 24 h involve Dectin-1, SYK, MAPKs donors and transcription factors AP-1 and NF-kB GITRL protein Murine DCs whole β glucan particles from (Tian et al, 2012) TNFSF18is the gene for GITRL, S. cerevisiae treated for 48 h a cytokine in the TNF ligand (100 µg mL…”
Section: Rela Relb Nfkb2 Nfkb1 Eb13 Cflar Btg1 Basp1 Atf4 Aimentioning
confidence: 99%
“…While most studies have focused on the activation of gene expression in DCs, a recent report demonstrated that purified β-glucan (curdlan) induces expression of several cytokines including TNFα, IL-6 andIL-8 in human B lymphocytes at both the mRNA and protein level (Ali et al, 2015). Activation of IL-8 was shown to be mediated through the Dectin-1 receptor and involved SYK, ERK and JNK and activation of the transcription factors AP-1 and NFκB.…”
Section: β-Glucans Induce Cytokine Production In Human B Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the diverse glucans present in mushrooms are α-glucans, which have also been identified in parasitic and bacterial cell communities (14). Notably, glucans have been indicated to increase the secretion of a range of key cytokines, including interleukins (ILs) and interferons (IFNs) (15,16). Our group previously demonstrated the anticancer and immunomodulatory activities of a glucan from CV with potential as a therapeutic in cancer treatment (3).…”
Section: Introductionmentioning
confidence: 99%